Persistent Hypoxemia in a Teen With Down Syndrome - Upchurch, Andrew (J Clin Sleep Med, 2019)
Upchurch A, Sharma S, Hadigal S, Wagner M, Berry R. Persistent hypoxemia in a teen with down syndrome. J Clin Sleep Med. 2019;15(10):1547–1549.